Transfers from the Earth to L2 Halo orbits in the Earth–Moon bicircular problem - Rosales, José J.; Jorba, Ángel; Jorba-Cuscó, Marc (Springer Science and Business Media B.V., 2022)
This paper deals with direct transfers from the Earth to Halo orbits related to the translunar point. The gravitational influence of the Sun as a fourth body is taken under consideration by means of the Bicircular Problem (BCP), which is a periodic time dependent perturbation of the Restricted Three Body Problem (RTBP) that includes the direct effect of the Sun on the spacecraft. In this model, the Halo family is quasi-periodic. Here we show how the effect of the Sun bends the stable manifolds of the quasi-periodic Halo orbits in a way that allows for direct transfers.
Keywords: bicircular problem; earth–moon transfers; invariant manifolds of tori; quasi-periodic halo orbits; translunar point; Scopus; JCR